Gaining pounds by losing pounds: preferences for lifestyle interventions to reduce obesity. Issue 2 (28th October 2014) - Ryan, Mandy; Yi, Deokhee; Avenell, Alison; Douglas, Flora; Aucott, Lorna; van Teijlingen, Edwin; Vale, Luke
Abstract While there is evidence that weight-loss interventions reduce morbidity, indications of their acceptability are limited. Understanding preferences for lifestyle interventions will help policymakers design interventions. We used a discrete choice experiment to investigate preferences for lifestyle interventions to reduce adult obesity. Attributes focused on: the components of the programme; weight change; short-term and longer-term health gains; time spent on the intervention and financial costs incurred. Data were collected through a web-based questionnaire, with 504 UK adults responding. Despite evidence that dietary interventions are the most effective way to lose weight, respondents preferred lifestyle interventions involving physical activity. While the evidence suggests that behaviour change support improves effectiveness of interventions, its value to participants was limited. A general preference to maintain current lifestyles, together with the sensitivity of take up to financial costs, suggests financial incentives could be used to help maximise uptake of healthy lifestyle interventions. An important target group for change, men, required more compensation to take up healthier lifestyles. Those of normal weight, who will increase in weight over time if they do not change their lifestyle, required the highest compensation. Policymakers face challenges in inducing people to change their behaviour and adopt healthy lifestyles.